International Students’ Vocabulary Learning Strategies at the English Language Intensive Course for Overseas Students’ Program - Suci Fitriani; Febria Sri Artika (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The purpose of this research is to investigate the Vocabulary Learning Strategies (VLS) employed by international students who are studying English as a second language at the English Language Intensive Course for Overseas Students Program (ELICOS) of the University of Canberra College English Language Centre (UCCELC) in Australia. A qualitative design was used to gather information from six international students from different countries including Indonesia, China, Philippine, and Japan by using interviews. The results from the interview were then analyzed and presented by using the qualitative research procedures including coding, grouping, argument construction, and drafting. The finding of this research revealed that students at the ELICOS program employ various VLS including cognitive, metacognitive, memory, and social strategies. Cognitive strategies are identified as the most popular strategies used by the students, followed by metacognitive and memory strategies respectively and social strategies are recognized as the least popular. These findings have important implications in improving the quality of language teaching and learning process and enriching the research repertoire in the field of VLS. Penelitian ini bertujuan untuk mengetahui strategi pembelajaran kosa kata yang digunakan oleh mahasiswa internasional yang sedang mempelajari bahasa Inggris sebagai bahasa kedua di English Language Intensive Course for Foreign Students Program (ELICOS) di University of Canberra College English Language Centre (UCCELC) di Australia. Desain kualitatif digunakan untuk mengumpulkan informasi kepada enam siswa internasional dari berbagai negara termasuk Indonesia, Cina, Filipina, dan Jepang dengan menggunakan wawancara. Hasil wawancara kemudian dianalisis dan disajikan dengan menggunakan prosedur penelitian kualitatif meliputi pengkodean, pengelompokan, penyusunan argumen dan penyusunan. Temuan penelitian ini mengungkapkan bahwa siswa pada program ELICOS menerapkan berbagai strategi pembelajaran kosakata termasuk strategi kognitif, metakognitif, memori dan sosial. Strategi kognitif diidentifikasi sebagai strategi paling populer diikuti oleh strategi metakognitif dan memori masing-masing dan strategi sosial diakui sebagai yang paling tidak populer. Temuan ini memiliki implikasi penting dalam meningkatkan kualitas proses belajar mengajar bahasa dan memperkaya khasanah penelitian di bidang strategi pembelajaran kosa kata.